Predicting Factors Affecting Glucose Monitoring Treatment Satisfaction and Drug Attitude Inventory (Adherence) Among Patients with Type 2 Diabetes Mellitus; Cross-sectional Observational Study - Rahman, Syed A. u. (Current Diabetes Reviews, 2019)
Objectives: The study aimed to explore the predictors affecting patient satisfaction to glucose monitoring system (GMSS) and drug attitude inventory (DAI) / treatment adherence among type 2 diabetes mellitus patients. Methods: Cross-sectional observational study design was used to conduct this study. Subjective assessments were made by questionnaires and objective data was collected from the patients' medication profiles registered to diabetic clinics. Patients were recruited from five different public hospitals of Hyderabad region, India. A total of 430 patients completed for analysis. The predictors to GMSS dimensions and adherence status were analyzed with Wilks's lambda effect and multivariate generalized linear model (GLM/MANOVA). Results: Study population consisted of 64.4% males and 35.6% females, age mean ± SD (43.3±11.42) years, majority of the study of participants were in between 40-60 years of age (53.3%). Majority of participants were considered healthy on BMI scale (67.2%), in contrast 234 (54.4%) reported high glycemic index with Hb1Ac (> 7.5%). Descriptive distribution pattern showed 241 (56.1%) participants were moderately satisfied with the current monitoring system. However, 157 (36.5%) reported poor satisfaction to GMSS scale score. Findings showed that low mean score of openness and worthwhileness are reported among nonadherent participants. Behavioral burden significantly high among nonadherent patients then adherents. However, emotional burden showed no effect on treatment adherence. Conclusion: This study found high rates of poor glucose monitoring system satisfaction along with low-to-poor treatment adherence among T2DM patients. Individual characteristics and clinical parameters significantly and positively predict the variance of GMSS and DAI among patients' with T2DM.
Keywords: Type 2 diabetes mellitus